Tata Laksana Komprehensif Terkini Penanganan Re-Emergensi Hand, Foot, and Mouth Disease (HFMD) di Indonesia: Tinjauan Lingkup: Tinjauan Pustaka - Putra, Muhammad Alifian Remifta (PT Kalbe Farma Tbk., 2024)
Hand, foot, and mouth disease (HFMD) is an exanthematous disease with the main manifestation of a maculopapular rash eruption on the hands, feet, and mouth accompanied by fever with potentially serious complications in children under five-years-old. Indonesia has a recurring cycle of HFMD outbreaks, making it a re-emergent disease. The author conducted a systematic search in three databases, including Pubmed, Wiley Online Library, and Science Direct, with the keywords